The stability of 99mTc-MIBI (Sestamibi) complex samples which prepared under ultrasound irradiation technique versus boiling water bath method - Alireza Doroudi, Farkondeh Saraji, Mostafa Erfani, Seyyed Mostafa Saadati, Ali Kisast, Faramarz Ahmadi, Behrooz Etesami (Journal of Applied Pharmaceutical Science, 2016)
Objectives: The main propose of this investigation is to evaluate the value of ultrasound irradiation technique versus boiling water bath in the reconstitution cold MIBI (Sestamibi) kits by technetium 99m. Material and Methods: Twenty Sestamibi cold kits from various batches have been chosen. The vials were randomly divided into two equal groups. The first group was reconstituted by boiling water bath as standard method and the other group reconstituted by new developed technique. The stability of radio-complex samples were examined by thin layer chromatography (ITLC) and Radio high pressure liquid chromatography (Radio-HPLC) up to 24 hours post reconstitution. The partition coefficient and protein bonding of radiotracer samples were analyzed. Results: The significant differences have not been observed in the yields and stability of radiotracer samples which were prepared by either two methods in ITLC and Radio-HPLC investigations. The partition coefficient and protein bonding assays demonstrated that radiotracer samples which were prepared by boiling water bath were a little more lipophilic than the radio-complex samples which were reconstituted by new developed technique. Conclusion: Green chemistry is convenient and efficient modality to reconstitute the cold Sestamibi kit by technetium 99m. It can be established as an alternative method to prepared 99mTc-Sestamibi in the clinical practice.
Keywords: Green chemistry,MIBI,Sestamibi,99mTc-MIBI,Ultrasound irradiation.